The influence of self-reflection towards counselor trainee self-development - Alis, Norzaliza; Wan Jaafar, Wan Marzuki; Mohd Ayub, Ahmad Fauzi (IDOSI Publications, 2014)
The study on the self-reflection among counselor training has not been conducted comprehensively in Malaysia. Even though self-reflection is very important in counselor development, it is a unique process whereby counselors can reflect on intrapersonal, interpersonal and clinical issues that influences their work. This process will be able to assist counselors in understanding how and when their personal attitudes, feelings and personal values influence the counseling process, besides acting as a guidance in their work. This study examined the development of counselor trainee influenced by self-reflection. A sample of 100 counselor trainee from four university who are undergoing internship training participated in the study. Using quantitative methodology, measures include self-reflection (self-awareness and management strategies) and self-development. The study found that self-development correlated negatively with self-awareness (r = -.249, p =. 012 ), but positively with management strategies (r =. 632, p =. 000).